FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN : (Studi Pada Badan Pemeriksa Keuangan Perwakilan Provinsi Lampung) - Petricia, Vina; Soedarsa, Herry Goenawan (Politeknik Negeri Ambon, 2023)
The ability of an auditor to detect fraud is no longer a kept secret. One of the auditor's abilities, and hence one auditor's qualities, is to detect fraud and explain abnormalities throughout the audit. This ability is supported by the auditor's understanding of the different types of fraud, their characteristics, and how to detect them. However, due to a variety of factors, many auditors fail to detect fraud. As a result, this study was conducted to empirically prove the influence of Red Flags, Time Pressure, Professional Skepticism, Competence, Independence, and Professionalism. The population in this study is the entire target population of BPK Representatives of Lampung Province auditors. Saturation sampling to obtain a sample of 48 questionnaires from all those distributed, with 35 respondents responding. The analytical method used was descriptive analysis using the IBM SPSS Statistics 26 application. The findings of this study show that Red Flags, Professional Skepticism, Competence, Independence, and Professionalism all have a positive and sig influence. On the other hand, the results of the Time Pressure variable have no positive and insignificant effect on the auditor's ability to detect fraud.